CONTEMPORARY DA’WAH BROADCASTING MANAGEMENT: COMPETITIVE STRATEGIES OF ISLAMIC TV STATIONS AND YOUTUBE CHANNELS IN RETAINING AUDIENCES - Adriansyah Muftitama; Ali Al-Jubouri; Murtadha Ibrahim (Journal International Dakwah and Communication, 2025)
The rapid digitalization of religious engagement has precipitated an intense rivalry between established Islamic television stations and emerging YouTube channels. This study investigates the competitive management strategies employed by these entities to optimize audience retention within a saturated media landscape. Adopting a qualitative comparative case study design, the research analyzes operational workflows and engagement metrics from national TV networks and high-performing digital channels. Data were gathered through in-depth interviews with station managers and content creators, supplemented by secondary analysis of digital analytics. The results identify a stark strategic divergence: television stations remain constrained by rigid, supply-side bureaucratic models that yield declining viewership, whereas YouTube channels utilize agile, demand-side strategies to achieve superior retention. Specifically, digital entities leverage real-time algorithmic feedback to maximize engagement, a competency largely absent in traditional broadcasting. The study concludes that the sustainability of contemporary Da’wah broadcasting depends on shifting from capital-intensive infrastructure to data-driven managerial agility. These findings offer a novel framework for “Algorithmic Da’wah Management,” suggesting that institutional authority is no longer sufficient without the integration of adaptive digital strategies to capture the modern viewer’s attention.